Effects of serial swabs on the nasopharyngeal mucosa: our experience in SARS-CoV2 screening - Dell’Aversana Orabona, Giovanni; Abbate, Vincenzo; De Fazio, Gianluca R; Calvanese, Carlo; Vaira, Luigi; Bonavolontà, Paola; Romano, Antonio; Improta, Giovanni; Piombino, Pasquale; Califano, Luigi (The Journal of Infection in Developing Countries, 2024)
Introduction: The purpose of the study was to analyze the effect of swabs on nasal mucosa. Methodology: Since May 2020, our department was responsible for screening coronavirus disease 2019 (COVID-19) among the employees of a company that continued its activity during the pandemic. The screening protocol consisted of two swabs per week. The samples were analyzed through objective endoscopic and subjective clinical evaluations with sino-nasal outcome test (SNOT Test) at three time points (T0, T1 - three months, T2 - six months). Results: 23.76% of patients showed an increase in the SNOT score at T1, and the score decreased at T2. This could be due to the phenomenon of "adaptation" of the nasal mucosa. Endoscopic control showed that at T1, secretion, hyperemia, and edema are the most common signs. At T2, however, the crusts accounted for 52.94% of all damage. It is evident that at T1 the endoscopically detected signs of "acute" damage were more represented than at T2, while the signs of "chronic" damage increased as the number of swabs increased. Conclusions: We demonstrated that mucosal damage and perceived symptoms were absolutely acceptable compared to the diagnostic advantage obtained with serial screening.